Grinding treatment effect on rib-to-roof weld fatigue performance of steel bridge decks. (February 2017) - Fu, Zhongqiu; Ji, Bohai; Kong, Xiangming; Chen, Xiang
Abstract: To study the effect of grinding treatment on deck fatigue performance of U-rib and roof welds in steel bridge decks, eight specimens of U-rib and roof welds were manufactured. The shape and metallography of welded specimens were measured to ascertain their form, characteristics, and microstructure after grinding. The effects of weld grinding treatment on stress distribution and fatigue life were investigated by fatigue tests. The influence of grinding radius and depth on the local stress field was studied by finite element analysis, and suggestions for grinding treatment related to the gouge radius and depth were proposed. The results indicated that grinding treatment effectively increased the transitional radius of the welds and reduced the stress concentration thereon without changing the local microstructure. Local cracking resulted in stress redistribution with no change in the ultimate bearing capacity of the welds. Grinding treatment redistributed the stress on the U-rib to the deck weld, which improved the fatigue life thereof. Grinding treatment caused a reduction in the thickness of the deck, which resulted in an increase in bending stress. However, the stress concentration at the weld toe was diminished. The maximum stress was located at the bottom of the gouge after grinding and it decreased with increasing grinding gouge radius and increasing grinding gouge depth. The grinding treatment gouge sizes were suggested as 3 mm (radius) and 0.5 mm (depth). Graphical abstract: Highlights: Propose to apply grinding treatment in fatigue maintenance of steel bridge Effects were proved by geometrical change, microstructure, fatigue tests and FEM. Advantage of geometrical shape and disadvantage of thickness decrease were compared. Reasonable sizes of grinding gouge were suggested.